Mao. 18 - Takahashi, Rumiko, 1957-; Roman, Annette (Shōnen Sandē komikkusu., 2024)
"Nanoka and Mao attempt to mediate a deadly dispute between curse-wielding sisters Kagari and Ayame. Then, our exorcist heroes are off to investigate villagers rumored to perform human sacrifices to a mysterious water god. Is Nanoka's sword, Akanemaru, up to the tasks that lie ahead...?"--Back cover.